ANALISIS VALIDITAS DATABASE STOCK OPNAME BMP GUNA MENDUKUNG KEBUTUHAN BMP JATAH DARAT DI STASIUN PENGISIAN BAHAN BAKAR TNI (SPBT) MABESAL - Dading Yudis Hamiseno; Daniel Setiawan; Geger Jaka Kiswara (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to analyze the problem of network failure which causes the barcode scanner not to function normally at SPBT Mabesal, calculation of depreciation and sounding of land storage tanks at SPBT Mabesal and weaknesses in the E-BMP application in terms of BMP distribution at SPBT Mabesal. In this study, researchers used a qualitative method type research approach. Data sources consist of two kinds, namely, primary data sources and secondary data sources. Data collection techniques using observation, interviews with research subjects and documentation studies. Data processing can be done using the NVivo software. The data analysis technique used in this study is the SSM (Soft Systems Methodology) method, which is an action research process, namely CATWOE (Clients, Actors, Transformation, Weltanschauung, Owner, Environment). The research results obtained are network failure problems that cause the barcode scanner not to function normally at SPBT Mabesal, calculation of depreciation and sounding of land storage tanks at SPBT Mabesal and weaknesses in the E-BMP application in terms of BMP distribution at SPBT Mabesal.